Nine new species of the genus Rosalba (Coleptera, Cerambycidae, Lamiinae, Apomecynini) from South America - Galileo, Maria Helena M.; Martins, Ubirajara R. (Zootaxa, 2013)
New species of Rosalba Thomson, 1864 are described: from Venezuela, R. jolyi sp. nov. (Aragua); from Colombia, R. maculosa sp. nov. (Santander); from Ecuador, R. mediovittata sp. nov. (Manabi), R. cacapyra sp. nov. (Orellana) and R. parvula sp. nov. (province unknown); from Bolívia, R. tanimbuca sp. nov. (Santa Cruz-); from Brazil, R. amazonica sp. nov. and R. gounellei sp. nov. (Amazonas) and R. vanini sp. nov. (Rondônia). R. malleri (Melzer, 1934) and R. digna (Melzer, 1934) are illustrated and new records are provided.